Optimizing tropical dairy goat diets: balancing rumen degradable protein, non-fiber carbohydrates, and sulfur requirements - Idat Galih Permana; Annisa Rosmalia; Febby Yustika Anggarini; Despal Despal; Toto Toharmat; Dwierra Evvyernie (Animal Bioscience)
Objective This study aimed to investigate the effects of rations incorporating rumen degradable protein (RDP), non-fiber carbohydrate (NFC), and sulfur on nutrient utilization, milk production, milk quality, and the economic aspects of dairy goats. Methods In the first study, five treatments were tested in a block-randomized design to examine in vitro fermentability and digestibility. Treatments included P0 (control diet), P1 (P0+7.5% cassava-NFC), P2 (P0+7.5% cassava-NFC and 5% soybean), P3 (P0+7.5% cassava-NFC and 5% autoclaved soybean), and P4 (P0+7.5% cassava-NFC, 5% autoclaved soybean, and 0.1% sulfur). In the second study, sixteen lactating Saanen-Ettawa crossbreed dairy goats (initial milk production = 0.97±0.25 L/head/d, 30 DIM; body weight = 44.44±7.20 kg) were assigned into four groups and fed treatment diets: R0 (basal diet), R1 (R0+12% autoclaved soybean), R2 (R0+12% autoclaved soybean and 9% cassava-NFC), and R3 (R0+12% autoclaved soybean, 9% cassava-NFC, and 0.11% sulfur). The diets were offered for 7 weeks with a two-week adaptation period. Parameters observed include milk production and quality, milk fatty acids, blood hematology and metabolites, and economic aspects. The study used a block randomized design with initial weight as a block. Results The treatment diets in the first study had no effect on in vitro fermentability and digestibility. Treatments R2 and R3 resulted in higher milk production than R0 and R1. Milk quality remained consistent across treatments, while solid non-fat, lactose, and protein was higher in R2 and R3. Blood hematology was unaffected by the treatments. Nutrient efficiency and income over feed cost were enhanced by R2 and R3 treatments. Conclusion Protected RDP using autoclaved soybean and cassava-NFC maintained in vitro digestibility, even though it did not improve in vitro fermentability. Precision dairy ration based on RDP, NFC, and sulfur positively impacts milk production, nutrient efficiency, and animal health in dairy goats.